Classical control theory for congestion avoidance in high-speed Internet - S. Mascolo (Proceedings of the 38th IEEE Conference on Decision and Control (Cat. No.99CH36304), 1999)
The explosive growth of the Internet with the ever-increasing demand for network bandwidth makes the issue of congestion control critical. In this paper, we use classical control theory to model the congestion control algorithm of the Internet’s Transmission Control Protocol (TCP) and the Smith principle to design a new algorithm for congestion control for the high-speed Internet. The analysis provides a theoretical insight into the congestion control mechanisms of TCP, along with a method to modify and improve this mechanism in a way that is backward-compatible, The proposed control algorithm generalizes today’s TCP congestion control algorithm using a generalized advertised window which is obtained by means of round-trip time measurements.
Keywords: Control theory; Internet; Protocols; Communication system control; TCPIP; IP networks; Feedback; Telecommunication network reliability; Propagation delay; Quality of service